FORMALISME KEHIDUPAN BERAGAMA (Studi Kasus Gereja Katolik Keuskupan Purwokerto) - Suraji, Robertus (LOGOS, 2017)
Indonesia is a nation that seems religious. Place of worship was flooded with a lot ofpeople. Events and holy days of religius became a national event. In the other hand,some times the religious comprehention was halted at the places of worship that wasit. In the national and society life easily we can find people to do things that arecontrary to religious values. Human rights violations and corruption becomes difficultto eradicate. Moral degradation occurs from the level of family, community, societyand state officials. Within communities also repeatedly occurred certain group usereligion as an instrument of legitimacy to the acts of violence driven by a belief in theirown truth as the only truth, and the loss of a sense of respect for those who areconsidered different. Hence people are not so concerned with the behavior that iscontrary to what religion had been teaches, even assume it was not related to faith. Onthe other hand there are people who are aware of the true situation but are powerless,or do not have enough courage to reject it. This is the situation called formalism ofReligious Life. The cause of religious formalism that may arise from the internalreligious teachings, not only from the social structure of society but also of a culturethat is built in this community. The impact of these religious formalism can happen ona personal level, both the social structure and the culture of the society. Therefore, tocounter religious formalism is not enough left to religious leaders, but also thereshould be a joint motion to change the structure and culture of Indonesian society.